2023
DOI: 10.3390/ph16010115
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Induces Apoptosis in Human Pancreatic Cancer (PC) Cells Accompanied by Changes in the Levels of Histone Acetyltransferases (Particularly, p300/CBP-Associated Factor (PCAF) Protein Levels)

Abstract: Accumulating evidence (mainly from experimental research) suggests that metformin possesses anticancer properties through the induction of apoptosis and inhibition of the growth and proliferation of cancer cells. However, its effect on the enzymes responsible for histone acetylation status, which plays a key role in carcinogenesis, remains unclear. Therefore, the aim of our study was to evaluate the impact of metformin on histone acetyltransferases (HATs) (i.e., p300/CBP-associated factor (PCAF), p300, and CBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…We first found that M-CDs caused profound cytotoxicity, initiating low cell viability against control cells even metformin-treated cells. These data support previous findings in the literature that indicated metformin caused a reduction in cell viability in different cells [19,20]. Our results have several similarities with previous findings, which indicated that CDs can reduce the viability of cells and induce cell death [21,22].…”
Section: Discussionsupporting
confidence: 93%
“…We first found that M-CDs caused profound cytotoxicity, initiating low cell viability against control cells even metformin-treated cells. These data support previous findings in the literature that indicated metformin caused a reduction in cell viability in different cells [19,20]. Our results have several similarities with previous findings, which indicated that CDs can reduce the viability of cells and induce cell death [21,22].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, metformin can suppress the expression of YAP/TAZ in various cancers, including PDAC, through AMPK-mediated mechanisms [346]. Recent research has also demonstrated that metformin induces apoptosis in pancreatic cancer cells by downregulating PCAF proteins [347].…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…In 2018, a revelatory approach showed that the EMT inducibility that is dependent on the molecular axis GLO1/TGFβ1/SMAD, by loss of the tumor suppressor miR-101, could be reversed by metformin administration in human invasive cells [80]. Interestingly, in recent years, metformin has been reported by several authors to target EP300 by at least different mechanisms including the following: (1) inhibition of H3K9 acetylation activity [81], (2) blocking the formation of E300-inducible phase separation condensates [82], or (3) direct modulation of EP300 mRNA levels [83], which will surely contribute to novel anti-proliferative and anti-invasive therapies based on EP300-dependent molecular mechanisms.…”
Section: Epithelial-to-mesenchymal Transition and Tgfβ Crosstalkmentioning
confidence: 99%